" ... then he ate my boy entrancers" - Rennison, Louise (London Harper Collins Publishers, 2005)
Hilariously funny Louise Rennison's fabby sixth book of the confessions of crazy but lovable teenager Georgia Nicolson. Guaranteed to have the nation laughing their knickers off!
Keywords: Dating (Social customs) -- England -- Interpersonal relations